Using rubrics to improve student writing - Hampton, Sally
Developed as part of the influential New Standards project, Using Rubrics to Improve Student Writing gives you everything you need to design and improve your writing instruction. Each section opens with a discussion of a genre common in school writing assignments: narrative, report of information, instructions, and response to literature. Then, the book presents detailed rubrics that illustrate what elements and strategies writing in that genre should display. With these rubrics, you'll have the tools you need to deliver formative assessment that will guide your instruction and support the young writers in your classroom